Osteomyelitis Pubis After Initiation of an SGLT2 Inhibitor - Adriana Nadeau; Katherine Macarthur; Eliza Bullis (Annals of Internal Medicine: Clinical Cases)
Osteomyelitis pubis is a rare infectious entity that is often misdiagnosed. Early clinical suspicion and appropriate diagnostic workup are required to prevent a delay in diagnosis and to differentiate the disease from alternative noninfectious diagnoses such as osteitis pubis. Herein, we report a case of osteomyelitis pubis with delayed diagnosis in a patient who recently initiated an SGLT2 inhibitor before the onset of symptoms. The effect of SGLT2 inhibitors on the risk of this disease is unknown but may warrant further investigation, as this case highlights.